Anchors of the Self: Cultivating Life Longings (Sehnsucht) and Goals in LGBTQ+ Therapeutic Discourse - Sharon Eli (International Journal of Psychotherapy Practice and Research, 2026)
We have highlighted the significant harm caused by internalized homophobia in LGBTQ+ individuals and the dimensions of internalized identity that often dim and redirect Motivations and Longings for a meaningful and valuable life for individuals in the LGBTQ+ community. We surveyed the dimensions of Life Goals and Longings as a basis for building motivation and a sense of worth in the individual, which forms the foundation of emotional well-being. From the perspective of the need for Longings and Life Goals, we identified relevant focal points in empowering work to establish these anchors within LGBTQ+ individuals. This process primarily focuses, alongside interpersonal and social dimensions, on the internal feelings associated with an individual's sense of identity. We emphasized the importance of having unique, personally tailored Longings for LGBTQ+ clients that are rooted in the dimensions ('virtues') of what is called 'character.’ As Hammack and Toolis (2014) articulated, we did not focus on others' perceptions of the LGBTQ+ individual as the sole central factor in constructing an individual's sense of self-esteem, although it is an important factor. Instead, we focused on the view that LGBTQ+ individuals mainly construct their self-esteem based on their perception of their values relative to those of society around them. An individual's values and Goals are at the center of constructing their sense of self-esteem when compared to society’s ‘correct' Goals. Individuals see themselves in character traits, less so in terms of function, in relation to their environment, and thus define their self-esteem as being 'good' or 'bad' in their own eyes 666467.
Keywords: Sehnsucht (life longings)